S193. EFFICACY AND SAFETY OF TRANSCRANIAL DIRECT CURRENT STIMULATION FOR TREATING NEGATIVE SYMPTOMS IN SCHIZOPHRENIA: THE FOLLOW-UP PHASE. (18th May 2020) - Valiengo, Leandro; Serpa, Mauricio; Elkis, Helio; van de Bilt, Martinus; Lacerda, Acioly; Gattaz, Wagner; Brunoni, Andre
Abstract: Background: Schizophrenia is a severe mental illness presenting a substantial, increasing burden. Its negative symptoms include flattened affect, loss of interest, and emo- tional withdrawal and are associated with poor functional outcomes. Most antipsychotic drugs are not effective for such symptoms and present important adverse effects3 and low tolerability. v Nonpharmacological interventions are also limited. Transcranial direct current stimulation (tDCS) is a noninvasive neuromodulatory technique that presents low costs, portability, ease of use, and no serious adverse effects. The technique injects weak, direct currents via scalp electrodes. A current fraction penetrates the brain, increasing or decreasing the neuronal excitability of regions near the anode or the cathode, respectively. Mimicking rTMS studies, tDCS trials have used anodal stimulation over the left PFC aiming to ameliorate negative symptoms. In a seminal study, Brunelin et al used a frontotemporoparietal montage in 30 patients with schizophrenia and demonstrated large effect sizes for improvement of negative symptoms and auditory hallucinations (AHs). Recently, we confirmed that active tDCS is more effective than sham tDCS for the negative symptoms of schizophrenia in a randomized, sham-controlled clinical trial with 100 patients. However, the studies showed tDCS efficacy only during the acute phase of the treatment of the negative symptoms of schizophrenia. In fact, as to understand tDCS' role in the therapeutic arsenal of schizophrenia, it is crucial to assess its efficacy during the continuation treatment. We performed a 24- week follow-up study to assess the relapse of patients presenting a clinical response after acute tDCS treatment. We also explored whether baseline clinical and demographic characteristics were predictors of relapse. Finally, we report the results of patients from the open-label, crossover phase of the study. Methods: The follow-up phase was the open-label in which all responders (>20% negative PANSS improvement or negative PANSS < 20) who had previously received active-tDCS were enrolled to a 24-week, follow-up phase in which a maximum of 9 tDCS sessions were performed – every other week for 3 months and, thereafter, once a month for the subsequent 3 months – sessions would be interrupted earlier whether the subject relapsed. TDCS was applied at 2mA/30-min, with the anode over the left dorsolateral prefrontal cortex and the cathode over the tempoparietal junction. Relapse was the outcome measure. Results: We had 20 responder in the clinical trial to tDCS and more 12 out 29 in the cross-over phase (who were sham and entered in an open-label exactly as the original clinical trial). Of this 32, 27 accepted to participate in the follow-up phase. The survival rate per Kaplan–Meier analysis was 61%. Patients with treatment ultra-resistant presented lower 24-week survival rate as compared to nonrefractory patients (58% vs. 67%), but without statistical difference between groups(P < .5). Equivalents dosages use of haloperidol, clozapine use, number of hospitalizations or length of the schizophrenia were a predictor of relapse. TDCS was well tolerated and with few side effects Discussion: Patients after using tDCS for negative symptoms of schizophrenia presents a low rate of relapse when compared the use of tDCS for major depression. tDCS can be an alternative to the treatment of negative symptoms of schizophrenia at long-term.